Elevation of cortical C26:0 due to the decline of peroxisomal β-oxidation potentiates amyloid β generation and spatial memory deficits via oxidative stress in diabetic rats. (19th February 2016) - Shi, Y.; Sun, X.; Sun, Y.; Hou, L.; Yao, M.; Lian, K.; Li, J.; Lu, X.; Jiang, L.
Highlights: Decreased peroxisomal β-oxidation and increased C26:0 were found in diabetic brain. C26:0 was positively correlated with Aβ and MDA respectively in diabetic brain. Impaired peroxisomal β-oxidation may contribute to AD progression in diabetic rats. Abstract: Diabetes mellitus correlates with subsequent development of Alzheimer's disease (AD). An accumulation of very long chain fatty acids (VLCFAs) was observed in AD brains. We found previously that inhibiting peroxisomal β-oxidation by an inhibitor caused increases in VLCFA and β-amyloid peptide (Aβ) in the cortex and primary cultured neurons of rats. Therefore, we investigated whether there was an impaired peroxisomal β-oxidation and elevated VLCFA related to the increased Aβ in the diabetic brain. This study was conducted in a type 2 diabetic rat model induced by a high-fat diet and low-dose streptozotocin. A decrease in peroxisomal β-oxidation activity caused by down-regulated thiolase expression and a consequent increase in C26:0 were observed. Meanwhile, decreases in eicosapentenoic acid (EPA) and increases in oxidative stress [indicated by levels of malondialdehyde (MDA), and the protein expression of NOX4, p47 phox and HO-1], Aβ, and the expression of AβPP and BACE1, two proteins involved in Aβ production, were observed. C26:0 levels were positively correlated with Aβ and MDA. This work suggests that in addition to decreases in EPA, increases in C26:0 by impaired peroxisomal β-oxidation can be a potential risk factor contributing to the progression of AD in diabetic brains via inducing oxidative stress.